2011
DOI: 10.1080/10810730.2010.546490
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Test of the Materialist Framework for Understanding the General Population's Reaction to Nonpersonalized Genetic Health Messages

Abstract: Genetic health messages are increasingly prevalent in our society. The materialist framework of laypeople's genetic knowledge may provide a good basis for understanding the effects of such messages on preventive behavior and related health cognitions. This study provides an empirical test of the predictions of this framework. We presented 929 participants who were aware or unaware of the existence of genetic risk factors for salt sensitivity with either a genetic health message or a general health message abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The current approach to awareness messages could also be tested for different health issues, for example, in the area of cancer screening [43]. Investigating the impact of message components and affective and cognitive responses to messages on various aspects of behavioral intention and behavior itself, such as a visit to a doctor, a search for more information, and vigilance about early warning signals, is yet another avenue for further research.…”
Section: Discussionmentioning
confidence: 99%
“…The current approach to awareness messages could also be tested for different health issues, for example, in the area of cancer screening [43]. Investigating the impact of message components and affective and cognitive responses to messages on various aspects of behavioral intention and behavior itself, such as a visit to a doctor, a search for more information, and vigilance about early warning signals, is yet another avenue for further research.…”
Section: Discussionmentioning
confidence: 99%
“…Persistence of misunderstandings, despite realization of their inaccuracy, suggests that providers need to address not just cognitive facts but underlying emotional issues when caring for individuals and families. Although several recent studies have found that the general public holds a favorable view of diagnostic genetic testing, a significant lack of knowledge exists in understanding the basic principles of inheritance (Smerecnik, Mesters, de Vries, & de Vries, 2011).…”
Section: Discussionmentioning
confidence: 99%